2006
DOI: 10.1113/jphysiol.2006.112425
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal relays in double crossed pathways between feline motor cortex and ipsilateral hindlimb motoneurones

Abstract: Coupling between pyramidal tract (PT) neurones and ipsilateral hindlimb motoneurones was investigated by recording from commissural interneurones interposed between them. Near maximal stimulation of either the left or right PT induced short latency EPSPs in more than 80% of 20 commissural interneurones that were monosynaptically excited by reticulospinal tract fibres in the medial longitudinal fascicle (MLF). The EPSPs were evoked at latencies that were only 1-2 ms longer than those of EPSPs evoked from the ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
7
36
0
Order By: Relevance
“…Regarding the ipsilateral dCINs, this suggests the presence of crossed dCINmediated pathways from medullary reticulospinal neurons to contralateral trunk and hindlimb MNs. Similar crossed CINmediated pathways from pontine reticulospinal neurons to hindlimb MNs have been described in the anesthetized adult cat (Jankowska et al, 2003(Jankowska et al, , 2005(Jankowska et al, , 2006. Regarding the contralateral dCINs, our findings are in accordance with the suggested presence in the adult cat of a dCIN-mediated double-crossed pathway between medullary reticulospinal neurons and ipsilateral hindlimb MNs (Jankowska et al, 2003;Matsuyama et al, 2004b).…”
Section: Are Dcins Topographically Organized According To Their Reticsupporting
confidence: 81%
“…Regarding the ipsilateral dCINs, this suggests the presence of crossed dCINmediated pathways from medullary reticulospinal neurons to contralateral trunk and hindlimb MNs. Similar crossed CINmediated pathways from pontine reticulospinal neurons to hindlimb MNs have been described in the anesthetized adult cat (Jankowska et al, 2003(Jankowska et al, , 2005(Jankowska et al, , 2006. Regarding the contralateral dCINs, our findings are in accordance with the suggested presence in the adult cat of a dCIN-mediated double-crossed pathway between medullary reticulospinal neurons and ipsilateral hindlimb MNs (Jankowska et al, 2003;Matsuyama et al, 2004b).…”
Section: Are Dcins Topographically Organized According To Their Reticsupporting
confidence: 81%
“…The fibres are thought to contribute more to the control of axial trunk muscles than limb muscles [34]. Several studies have shown that TMS can elicit responses in ipsilateral muscles, preferentially in axial muscles [9,10,[35][36][37][38], but it remains uncertain as to whether these responses are transmitted by an ipsilateral corticospinal tract [39]. The difference in latency of the erector spinae MEPs observed in the present study indicates that two pathways may be involved.…”
Section: Corticospinal Tractsmentioning
confidence: 70%
“…Approximately 30% of the total number of FG-labeled neurons were found to be commissural, allowing us to speculate that approximately 30% of the axons in the ventrolateral white matter arise from commissural reticulospinal neurons. The existence of such pathways is supported by Jankowska et al (2006) who describe double-crossed pathways involving commissural reticulospinal neurons along with their ability to activate hindlimb motoneurons caudal to an ipsilateral thoracic spinal cord hemisection. Matsuyama et al (2004) also emphasized the point that monosynaptic reticulospinal inputs (originating from either side of the brainstem) can coordinate bilateral CPG-related activity via spinal commissural interneuronal circuits in the cat spinal cord.…”
Section: Reticulospinal Neurons Labeled From the Vlf At T9mentioning
confidence: 97%